Identification of Agriculture, Forestry, and Fisheries Sectors in Mitigating Income Inequality in the Former Residencies of Madiun - Maulida Nur Isnaini; Agustono; Umi Barokah (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2022)
Development is a long-term process of change to improve regional welfare. The regional economic development indicator is GRDP. The former Madiun residencies have the lowest average of GRDP. Accordingly, the economic development activities and effort to mitigate income inequality should be carried out properly. Using MRT, Williamson Index, and Shift Share analysis, the research results on agricultural, forestry and fisheries sectors of the former Madiun residencies include the basic and non-basic sectors. The basic-sector former residencies of Madiun include the regencies of Pacitan, Ponorogo, Madiun, Magetan, and Ngawi. Meanwhile, the non-basic sector ex-residence is the City of Madiun. The results of the Williamson Index show that the agricultural sector has a role in reducing income inequality. The IW value of ex-residencies with the agricultural sector has an average of 0.39, and the one without the agricultural sector is 0.53. As for the shift-share, the results show that the national share component of all sub-sectors is positive, meaning that sub-sector is experiencing growth. The industrial mix of all sub-sectors is negative (IM<0), meaning that sub-sector growth in former Madiun residencies is slow. The competitive share has positive value (CS>0), meaning that it has good sub-sector competitiveness and can develop.